2022
DOI: 10.1371/journal.pone.0270161
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic health literacy and associated factors among diabetes mellitus patients on follow up at public hospitals, Bale Zone, South East Ethiopia, 2021

Abstract: Objective This study was aimed to assess diabetic health literacy and associated factors among adult diabetic patients in public hospitals, Bale Zone, Southeast Ethiopia. Methods A hospital-based cross-sectional study was conducted among 402 diabetic patients in three public hospitals and the samples were selected using simple random sampling technique. The comprehensive functional, communicative, and critical health literacy questionnaire was used to measure diabetic health literacy. Descriptive statistics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 13 publications
4
9
2
Order By: Relevance
“…This study also revealed that having more than one source of information was positively associated with diabetic health literacy level. This result goes in lined with study done in bale (20), Having variety of sources of information was positively associated with diabetic health literacy. This might be due to a person with different sources of information will get different ideas about health and strengthen the previous knowledge.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study also revealed that having more than one source of information was positively associated with diabetic health literacy level. This result goes in lined with study done in bale (20), Having variety of sources of information was positively associated with diabetic health literacy. This might be due to a person with different sources of information will get different ideas about health and strengthen the previous knowledge.…”
Section: Discussionsupporting
confidence: 89%
“…This study has shown a signi cant association between social support and diabetic health literacy level. Similar nding was found in china and in Bale, Ethiopia (20,34), indicating that strong social support and high diabetes health literacy were highly associated. This might be due to, participants with strong social support share information they have learned from various sources and the other possible reason might be strong social support can contribute for positive mental and physical health that enable patients to work toward a long-lasting healthy lifestyle(38).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…However, no relationship was found between health literacy and intentional non-adherence, which includes stopping medications when feeling better or worse [44]. Studies show that LHL is connected with poorer disease knowledge and symptom recognition, poor glycemic or dyslipidemia control, greater difficulty interpreting food labels and estimating portion sizes, lower selfefficacy, higher level of body mass index, information gap in the use of medical devices for self-monitoring of blood glucose (SMBG), poorer communication with their providers, higher doses of insulin, more medical expenses and hospitalization among diabetes patients [45][46][47][48][49][50][51][52]. LHL is more common in people with hypertension and is associated with hypertension prevalence in selected ethnic groups [53].…”
Section: Medication or Treatment Guideline Non-compliancementioning
confidence: 99%